OPTIMIZING DIGITAL DISASTER RISK COMMUNICATION TO STRENGTHEN URBAN FLOOD RESILIENCE: INTEGRATING BIBLIOMETRIC AND QUALITATIVE APPROACHES IN MAKASSAR CITY (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Flood disasters continue to pose significant challenges to urban resilience in Makassar City, Indonesia, highlighting the urgent need for effective digital disaster risk communication. Despite the increasing use of digital platforms for disseminating disaster information, communication remains hindered by fragmented information, limited digital access, inadequate inter-agency coordination, and diverse levels of public digital literacy. This study aims to examine strategies for optimizing digital disaster risk communication to strengthen flood disaster resilience in Makassar City. A mixed qualitative design integrating bibliometric analysis and qualitative inquiry was employed. The bibliometric analysis was conducted to identify global research trends, conceptual structures, and collaboration networks related to disaster risk communication, while empirical data were collected through semi-structured interviews, observations, documentation, and Focus Group Discussions (FGDs) involving government agencies, disaster management institutions, communication authorities, environmental experts, and community representatives. Qualitative data were analyzed using NVivo 12 Plus through thematic coding and data triangulation. The bibliometric findings indicate that risk communication, community resilience, social media, and disaster risk reduction are dominant themes in global research. Meanwhile, the qualitative findings reveal that Makassar has adopted digital communication platforms for disaster management; however, their effectiveness remains limited due to fragmented communication systems, weak institutional coordination, and unequal digital access. Integrating the bibliometric evidence with the qualitative findings demonstrates that strengthening disaster resilience requires an integrated digital communication ecosystem supported by collaborative governance, interoperable information systems, enhanced digital literacy, and active community participation. This study contributes to disaster governance by proposing a comprehensive framework to optimize digital disaster risk communication in urban flood management.